Theophylline as an add-on to thrombolytic therapy in acute ischaemic stroke (TEA-Stroke): A randomized, double-blinded, placebo-controlled, two-centre phase II study. (December 2016) - Modrau, Boris; Hjort, Niels; Østergaard, Leif; Mouridsen, Kim; Andersen, Grethe; Bach, Flemming Winther
Introduction: Early reperfusion of brain tissue at risk of injury (penumbra salvage) is crucial in treating acute ischaemic stroke. Neuroprotective agents may extend the time window for the reperfusion. The vasoactive agent theophylline redistributes the perfusion to ischaemic brain tissue and thus reduces brain damage, brain tissue oedema and mortality in animal stroke models. Furthermore, treatment with theophylline has been shown to result in considerable and rapid clinical improvement, albeit only temporary, in some stroke patients. We hypothesize that treatment with theophylline will improve the collateral supply in acute ischaemic brain tissue and thus facilitate reperfusion despite proximal vessel occlusion. The primary study objective is to evaluate whether theophylline is safe and efficient in acute ischaemic stroke patients as an add-on to thrombolytic therapy. Methods: The TEA-Stroke Trial is a two-centre, proof of concept phase II clinical study with a randomized, double-blinded, placebo-controlled design. One hundred and twenty patients with acute ischaemic stroke and significant perfusion–diffusion mismatch, as determined by magnetic resonance imaging, are randomized 1:1 to either theophylline or placebo as an add-on to standard thrombolytic therapy. Study outcome: The dual primary outcome measures include penumbra salvage (penumbral tissue not developing into infarcted tissue) and clinical improvement at the 24-h follow-up. Discussion: Results from studies of theophylline in stroke animal models, clinical case series and randomized clinical trials are controversial. A Cochrane analysis from 2004 concluded that there was not enough evidence to assess whether theophylline is safe and improves outcomes in patients with acute ischaemic stroke. The TEA-Stroke Trial will clarify whether theophylline as an add-on to standard thrombolytic therapy improves penumbra salvage with a reduced risk of reperfusion damage, reduced final infarct size, and improved clinical outcome.